Analysis of the Use of Non-Cash (Cashless) as a Payment Tool among Generation Z in Indonesia - Jessica Sessi Amanda Sitompul; Khaira Amalia Fachrudin; Nursakti Sihotang; Ridwan Firmansyah; Yudika Navaloam (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Technological developments, especially in the use of cashless transaction systems, have increased. Cashless society is also overly concerned about efficiency and effectiveness as well as security. Indications of the high use of cashless have an impact that makes Generation Z begin to switch to financial management as a means of payment for development. This study examines the factors that influence the Purpose and Reasons for Using Cashless as a means of payment. Data were obtained as many as 200 from respondents who were able to fill out questionnaires, the respondents were all generation Z. This study used a quantitative approach. Data analysis was done by testing the classical assumption to see the normality of the data. The results of this study indicate that the benefits, convenience, risk, trust, product knowledge and compulsion have a significant influence on the Purpose and Reasons for Using Cashless (non-cash) as a means of payment.